EFFECT OF BIOMASS FUEL AND LPG ON PULMONARY FUNCTION IN RURAL WOMEN - K.SAROJINI (International Journal of Pharma and Bio Sciences, 2014)
The study was to compare the pulmonary functions in healthy ,nonsmoking women who used either biomass or liquefied petroleum gas (LPG) as cooking fuel. The effects of biomass fuel, type of ventilation, economic status and cooking index were also taken. The study of the effect of pulmonary function was investigated during the period of Jan 2007. Sixty healthy, non-smoking women were included 30 cooked solely with biomass and 30 cooked with LPG. A standardized respiratory symptoms questionnaire was administered to all the subjects and spirometry was carried out. Passive smoking showed significant difference between the two groups. Statistically significant differences were found in lung functions between two groups FVC, FEV1, FEV1% pred which was significantly lower (P<0.05) in study group, but FEV1%, FEF 25-75% & FEF 25-75% % pred no significantly difference but the value is less in women using biomass. The step-wise student‘t’ test analysis showed no correlation between cooking fuel and the pulmonary functions. The absence of the expected adverse effects of biomass on pulmonary functions was possibly due to better ventilation in the kitchens of subjects in the biomass group compared to previous studies.